Sorption Capacity of Pesticides on Soil in a Predominant Apple Cultivation Area. Issue 1 (2nd January 2020) - Kumari, Dev; John, Siby
ABSTRACT: Laboratory-based batch sorption experiments were performed using six pesticides and 12 soil samples collected from the predominant apple cultivation areas of Kinnaur district, Himachal Pradesh (India). Freundlich isotherm model was used to determine the sorption coefficients. Soil properties such as texture, pH, organic matter content (OM), cation exchange capacity (CEC), total dissolved solids (TDS), and clay content were measured for different soil samples. The principal component analysis showed that the sorption of pesticides was considerably affected by organic matter in the soil. Multiple linear regression models were proposed correlating the sorption coefficients and soil properties. The models and maps developed in this study could be used to estimate the mobility risk of pesticides and to evolve pesticide pollution management plans.